Mental health and mental capacity law for social workers : an introduction - Godefroy, Simon (Transforming social work practice., 2015)
Introduces students to the fundamental principles of mental health law and how they can be applied to everyday practice with clear introductions to key Acts such as the Mental Capacity Act and the Mental Health Act as well as the relevant Codes of Practice.